Search at the Margin - Carrasco, José A.; Smith, Lones (American Economic Review, 2017)
We extend search theory to multiple indivisible units and perfectly divisible assets, solving them respectively with induction and recursion. Buyer demands and prices are random, and the seller can partially exercise orders. With divisible assets, the Bellman value function is increasing and strictly concave, and the optimal reservation price falls in the position, reflecting increasing holding costs (opportunity cost of delaying optionality for inframarginal units). The marginal value exists, and is strictly convex with a falling purchase cap density. Our model is amenable to price-quantity bargaining; e.g., greater buyer bargaining power is tantamount to greater search frictions. (JEL C61, C78, D25, D83, G31)